Respostas

2013-11-25T17:58:25-02:00
1)     x - 2 √2 = 6x + 3 √2  x – 6x = 3 √2 + 2 √2  -5x = 5√2 (-1)    x = -5√2             5      X = -√2   2)     3x - 2 = -2/x + 1 3x  + 2/x =  1+ 2 (3x2 +2) /x=  3 3x2 +2  =3x 3x2 – 3x + 2 = 0 a = 3 b = -3 c = 2   ∆= b² -4ac = (-3)² - 4.3.2 = 9 – 24 ∆ = -5, portanto não possui raízes reais.         3)     6/x - 3 = -2/x + 1 6/x +2/x =  1+ 3 8/x = 4 8/x = 4/1 4x = 8.1  x = 8/4 x = 2   4)     6(x + 1) - 2(x - 3) = 5              6x + 6 -2x + 6 = 5              6x -2x = 5- 6 -6               4x =-7                 x= -7/4   5)     x+1 / x-3 = 5                x +1  -3 = 5                mmc = x                                                                                                                                                            x                x²+ 1 – 3x =  5x               x² – 3x -  5x + 1=0               x² - 8x  +1  = 0 a = 1; b  = -8 ; c = 1   ∆ = (-8)² - 4.1.1  = 64 – 4 = 60   x = -(-8) ±√60  = 8 ±√60   è x = 8 ± 2√15               2                2                      2   x = 2 ( 4± √15)è x’ =                   2 x’ = 4- √15 e  x’’ = 4 + √15
Feito no word e colado aqui